Bisnis Analisis Studi Kelayakan Bisnis Wedding Organizer (Studi Kasus pada “Rahma Wedding Organizer” di Kabupaten Pekalongan) - Nor Fatmah Rahmawati (CV. Kalimasada Group, 2023)
This writing aims to find out and analyze the business feasibility test of Rahma Wedding Organizer on market and marketing aspects as well as existing social and economic aspects. The approach used in this study is a qualitative descriptive method with primary data collection techniques from field research in the form of observations and interviews. The results of this study indicate that from the analysis of market, marketing, social and economic aspects, Rahma Wedding Organizer's business prospects are stated to be very good. This can be seen from the demand for services which is almost 24 hours a day, high consumer interest, relatively affordable price offerings, starting from packages of 40 million to 85 million, as well as various marketing mix strategies. When viewed from social and economic factors, Rahma Wedding Organizer's business development has a strong basis to be implemented, because the existence of Rahma Wedding Organizer can be a strong economic driver in the area of its business operations. Thus it can be concluded that from the various aspects that are the focus of research, Rahma Wedding Organizer's business can be said to be very good so that this business is feasible to run.